Three approaches to determining clinically meaningful benefit on the Cohen‐Mansfield Agitation Inventory in dementia clinical trials for agitation - Kathy Y. Liu; Chineze Ivenso; Rebecca Howard; Penny Rapaport; Suzanne Reeves; Sube Banerjee; Lon S. Schneider; Maria I. Lapid; Agitation MCID Study Group; Robert Howard (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION There is a need to understand the clinical meaningfulness of symptom score changes in treatment trials of dementia‐related agitation. We estimated minimal clinically important differences (MCIDs) for commonly employed agitation scales and contextualized their clinical application. METHODS We employed anchor‐ and distribution‐based approaches to determine changes in scores corresponding to minimal symptom improvement. An opinion‐based approach assessed expert clinicians’ agreement on the meaningfulness of score changes through three clinical vignettes. RESULTS Minimal symptom improvement for Cohen‐Mansfield Agitation Inventory total score ranged from −4 (over <1 month) to −11 (over 1 to 3 months) points. Greater symptom severity correlated with higher MCID estimates. The clinical importance of score changes was influenced by treatment duration, pharmacological side effects, and impacts on caregiver distress/time resources. DISCUSSION The clinical meaningfulness of agitation scale MCIDs is influenced by trial‐specific and clinical factors. Shorter trial durations and measuring caregiver distress/time resources enhance the clinical interpretation of agitation treatment outcomes. Highlights For the CMAI total score, the MCID was −4 points over shorter time scales and −11 points for longer time scales. Worse agitation severity was associated with higher MCID estimates. There was high expert consensus that a noticeable treatment benefit was not worthwhile if it occurred after 12 weeks or had no impact on caregiver/staff distress/time resources.